CHALLENGES OF ENGLISH TEACHERS AND STUDENTS IN IMPLEMENTING THE MERDEKA CURRICULUM - Eko Susilo Pompana; Rasuna Rasid Talib; Magvirah El Walidayni Kau (ADISAM Publisher, 2026)
This study investigates the challenges faced by English teachers and students in implementing the Merdeka Curriculum at SMA 2 Wonosari. Using a qualitative case study approach, data were collected through interviews, classroom observations, and document analysis. The findings indicate that teachers experience difficulties in lesson planning, classroom implementation, and assessment, particularly related to time management, student diversity, and limited facilities. Students also face challenges in adapting to student-centered learning and technology-based instruction. These findings suggest the need for continuous teacher training and institutional support to ensure effective curriculum implementation.